2017
DOI: 10.1016/j.ijggc.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A new polymer nanocomposite repair material for restoring wellbore seal integrity

Abstract: Seal integrity of functional oil wells and abandoned wellbores used for CO 2 subsequent storage has become of significant interest with the oil and gas leaks worldwide. This is attributed to the fact that wellbores intersecting geographical formations contain potential leakage pathways. One of the critical leakage pathways is the cement-shale interface. In this paper, we examine the efficiency of a new polymer nanocomposite repair material that can be injected for sealing micro annulus in wellbores. The bond s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…2930 Thus, a measure for the degree of crosslinking X link is adopted from Genedy et al. 20 as in equation (3). where X link is a measure of the degree of crosslinking of the polymer nanocomposite.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2930 Thus, a measure for the degree of crosslinking X link is adopted from Genedy et al. 20 as in equation (3). where X link is a measure of the degree of crosslinking of the polymer nanocomposite.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This was explained by the effect of nano-alumina particles on the curing behavior of the epoxy coating. Finally, recent investigation by Genedy et al 20 reported the ability of 0.5% ANPs to improve bond of Novolac epoxy to shale. Fourier transform infrared spectroscopy (FTIR) analysis of ANPs in Novolac epoxy proved that a chemical interaction of ANPs in epoxy takes place due to the amphoteric nature of ANPs.…”
Section: Introductionmentioning
confidence: 95%
“…At the middle of the layers are two active cells, which absorb stimulated light and emit electrons. One of these two compounds is chloroaluminium phthalocyanine, which serves as an organic electron donor, and the other is carbon 60 (C 60 ) electron receptor [18]. The thickness of phthalocyanine chloroalumine is 15 and C-60 is 30 nm.…”
Section: Light Emitting Nanoparticles; a Reasonable Way To Improve Thmentioning
confidence: 99%
“…Pada tahun 1995 dan 1996, lebih dari empat puluh tambalan (patch) telah dipasang di sumur uji yang dangkal di Rennes dengan berbagai kondisi lubang bawah permukaan [4]. Polimer superabsorbent dengan sifat khusus yang dapat menyerap dan menjaga sejumlah besar fluida encer pada kondisi panas dan tekanan tertentu dapat digunakan untuk mencegah/membatasi aliran fluida melalui kebocoran pipa [5].…”
Section: Pendahuluanunclassified
“…Pada tahun 1995 dan 1996, lebih dari empat puluh tambalan (patch) telah dipasang di sumur uji yang dangkal di Rennes dengan berbagai kondisi lubang bawah permukaan [4]. Polimer superabsorbent dengan sifat khusus yang dapat menyerap dan menjaga sejumlah besar fluida encer pada kondisi panas dan tekanan tertentu dapat digunakan untuk mencegah/membatasi aliran fluida melalui kebocoran pipa [5].Metode patch repair bukan merupakan suatu kegiatan yang mudah untuk dilakukan pada production tubing karena memiliki parameter-parameter tertentu yang harus dikontrol, seperti flow rate dan tekanan fluida serta temperatur production tubing. Selain itu, juga dibutuhkan biaya yang banyak untuk melaksanakan metode patch repair dalam mengatasi kebocoran tubing [6].…”
unclassified